An Exploratory Study of Risk Experience and Personal Values on Support for Climate Change Policies - Cara Lawson; Kiera Dwyer; Laura Morgan Fischer; Lauren Chase (Journal of Applied Communications, 2023)
In 2020 Oregon suffered one of the worst wildfire seasons on record that included a higher percentage of burned forest area, the destruction of residential areas, and significant risk to human health. The level of wildfire intensity was largely attributed as an effect of climate change, and future Oregon wildfire seasons are predicted to grow in intensity, acreage burned, and total duration. Public policy can be a tool to help to mitigate the effects of climate change, but successful policy implementation relies on public support. Therefore, this study sought to explore two factors that may influence support for climate change policy: risk experience and personal values. Oregon residents’ perceptions of and experiences during the 2020 Oregon wildfire season were assessed. Results indicated the value of universalism had a significant and substantial association with support for climate change policy, and power, achievement, stimulation, self-direction, and benevolence had significant low associations. Participants’ risk experience with wildfires accounted for little total variance in regard to support for climate change policy.
Keywords: climate change; wildfire; personal values; risk experience; policy support